Participative governance a descriptive study of proposed changes in administrative rules and procedures from St. Scholastica's College's tertiary students - Antonio, Michael G. (Journal of Action Research, 2014)
Sustainable institutions emerge from sound management practices, long term planning and the prudent use of available resources. These qualities however must be based on recognizing and addressing the needs of stakeholders. From the perspective of the college unit, students are stakeholders. Administration must take into account their inputs in making the institution better. The paper discusses several recommendations sourced from college students in terms of reforming utilized focus group discussions in generating data and synthesized by categorizing the data gathered by curriculum changes, facilities improvement and changes in rules and procedures.